Developing Comic Strip-Based Learning Media For Writing Assignments - Nuriyah Welia Purnama Sari; Istiqamah Ardila; M Saufi Rahman (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This research aims to develop comic strip as a media learning focused on improving the writing skills of seventh-grade students at MTsN 3 HSU. This media is designed to address issues found during the initial observation, such as students' low interest in writing, limited vocabulary, and difficulty understanding English sentence structures. The development of this media adopts the Research and Development (R&D) model proposed by Borg and Gall, with stages that include needs analysis, planning, development of the initial product, expert validation, initial trial, product revision, main field trial, and final revision. The developed media contains comics with an engaging adventure storyline, characters that match the students' characteristics, and is accompanied by writing tasks that train vocabulary usage, basic grammar, and sentence construction skills. The results of validation from media and material experts show that the developed comic strip meets the